REFLEKSI KETAUHIDAN DALAM WAYANG SADAT LAKON KI AGENG PENGGING - Hasan Ashari; Hermanu Joebagio; Musa Pelu (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Firstly performed in 1985 by Suryadi (a religious figure of Trucuk), Wayang Sadat is a medium to teach Tauhid (tawheed), the message of Islam. This research analyzes the teaching of Tauhid within Wayang Sadat performance, in the lakon (story) “Ki Ageng Pengging”. The sources of data were key informants, documents, and archives related to Wayang Sadat performance. The data were collected by interviews, the content of the performed lakon, depth examination of document and archives. The triangulation method was used to test the validity of the collected data. The data was analysed using the interactive model that consists of three stages: data reduction, data presentation, and data verification. The result of the research shows that the lakon “Ki Ageng Pengging” contains the teachings of Tauhid embedded in the janturan (narration), dialogues, lyrics of the music, and lyrics of sulukan (songs by the dalang – puppet master).